Four-year PhDs in neuroscience: an assessment after four years. - Rawlins, N; Akerman, C; Andolina, I; Blakemore, S; Mrsic-Flogel, T; Attwell, D (2000)
In 1996, as an innovation for the UK, the Wellcome Trust set up two 'American style' four-year PhD programmes in neuroscience, with an initial year of broad training followed by a three-year PhD. Here, some of the first cohort of students, who are soon to graduate and the coordinators of the programmes, give their views on this experiment in neuroscience research training.